Laboratorio di disegno Esercitazioni guidate al disegno di arredo - Moschillo, Raffaele (Strumenti per la didattica e la ricerca, 2005)
The present research on the theme of the design of furniture components starts from the didactic experience carried out within a Design Drawing Laboratory. The aim of the course is to apply the themes and methods related to representation and, at the same time, develop the graphic processing skills of each student. The text is divided into four sections: drawing as a science of representation, drawing as analysis, drawing as a communication tool, drawing as a project. Each single theme is then divided into a theoretical part and a corresponding practical part with one or more exercises.